Thyroseq V3 Molecular Profiling for Tailoring the Surgical Management of Hürthle Cell Neoplasms - Sarah Pearlstein; Arash H. Lahouti; Elana Opher; Yuri E. Nikiforov; Daniel B. Kuriloff (Case Reports in Endocrinology)
Hürthle cell predominant thyroid nodules often confound the diagnostic utility of fine needle aspiration biopsy (FNAB) with cytology often interpreted as a Hürthle cell lesion with an indeterminate risk of malignancy, Bethesda category (BC) III or IV. Molecular diagnostics for Hürthle cell predominant nodules has also been disappointing in further defining the risk of malignancy. We present a case of a slowly enlarging nodule within a goiter initially reported as benign on FNAB, BC II but on subsequent FNAB suspicious for a Hürthle cell neoplasm, BC IV. The patient had initially requested a diagnostic lobectomy for a definitive diagnosis despite a higher risk of malignancy based on the size of the nodule > 4 cm alone. To better tailor this patient’s treatment plan, a newer expanded gene mutation panel, ThyroSeq® v3 that includes copy number alterations (CNAs) and was recently found to have greater positive predictive value (PPV) for identifying Hürthle cell carcinoma (HCC), was performed on the FNAB material. Molecular profiling with ThyroSeq® v3 was able to predict a greater risk of carcinoma, making a more convincing argument in favor of total thyroidectomy. Surgical pathology confirmed a Hürthle cell carcinoma with 5 foci of angioinvasion and foci of capsular invasion.